Evaluation of non-conformities in the drafting of bulletins for urine cytobacteriological examinations at Sikasso Hospital (Mali) - Luka DIARRA; Moussa Mariko; Salif Traore; Safi Bazi Dicko; Aboudou Dolo; Moussa Coulibaly; Daouda Sidibé; Moumouni Daou; Hachimi Poma; Madou Traoré; Ibrahim Guindo (AboutScience Srl, 2024)
Background: Non-compliance in the drafting of examination bulletins makes it difficult to perform them and interpret the results. With the aim of continuously improving laboratory services and guaranteeing the quality of urine cytobacteriological examination (ECBU) results, we initiated this study to evaluate non-compliance in the drafting of ECBU reports. Materials and methods: This was a retrospective descriptive cross-sectional study which focused on non-compliance in the drafting of ECBU reports analysed in the laboratory from January to December 2022. Results: During the study period, we collected 383 non-compliant ECBU reports out of 672, with a frequency of 56.99%. Non-compliances were related to age (2.68%), profession (24.40%), clinical information (6.70%) and residence (52.08%). The majority of non-compliant reports came from the medicine (35.51%) and urology (25.85%) departments. Conclusion: The high frequency of non-compliance is a cause for concern and is of concern to all prescribers in this hospital.